Characterisation of the flow behavior of deep drawing steel grades in dependency of the stress state and its impact on FEA - Merklein, Marion; Sturm, Vera (International Journal of Material Forming, 2009)
In numerical simulation the flow behavior of the material is described by the flow curve under uniaxial stress condition. As within the tensile test experimental values can only be determined up to low strains, further experiments are applied in order to obtain higher strains. The alternative experiments are generally carried out under different stress conditions in comparison to the stress condition of the tensile test. Within this paper the differences in flow behavior under the respective stress conditions are figured out. Apart from the optical strain analysis of the tensile test after the onset of necking, the bulge test and the layer compression test are applied. Furthermore the work hardening of materials under different test conditions is compared. © Springer/ESAFORM 2009.
LFT Import::2019-07-29 (310)
Keywords: Deep drawing steel grades; Flow behavior; Stress condition

Effiziente Bewertung von Blechumformprozessen durch die Reduzierung kritischer Einflussgrößen in der stochastischen Simulation - Merklein, Marion; Sturm, Vera; Wahl, M. (Bauteile der Zukunft - Methoden und Prozesse - Tagungsband T31 des 30. EFB-Kolloquiums Blechverarbeitung am 2. und 3. März 2010 in Bad Boll, 2010)
LFT Import::2019-08-05 (311)

Einfluss von Chargenschwankungen auf die Verarbeitungsgrenzen von Stahlwerkstoffen - Sturm, Vera (Friedrich-Alexander-Universität Erlangen-Nürnberg, 2013)
Due to the increasing complexity of car body components, the process window of the forming process without defects is limited. Consequently, in serial production process even small variations of material properties may lead to rejections as a result of defects. Within this book a methodology is presented, capable of detecting the impact of significant varying material properties on the forming result in an efficient manner. As a result it shall be possible to design a robust process even at the time of process layou

Influence of the Variation of Material Properties on the Risk of Failure in Dependency of the Materials Flow Condition during Forming Processes - Sturm, Vera; Merklein, Marion; Bernhard, Oberpriller (International Journal of Material Forming, 2010)
LFT Import::2019-07-29 (314)
Keywords: Failure risk; Sheet metal forming; Variation of materials properties

Material Modelling for Stochastic Simulation - Sturm, Vera; Annen, C.; Merklein, Marion (Proc. 50th Conference of IDDRG 2010, 2010)
LFT Import::2019-08-05 (312)

Mechanical properties and plastic anisotropy of the quenchable high strengt steel 22MnB5 at elevated temperatures - Merklein, Marion; Lechler, Jürgen; Sturm, Vera; Bruschi, S.; Ghiotti, A.; Truetta, A. (Tagungsband SheMet'07, 2007)
LFT Import::2019-08-05 (1457)

Variation of deep drawing steel grades’ properties in dependency of the stress state and its impact on FEA - Sturm, Vera; Merklein, Marion (International Journal of Material Forming, 2011)
LFT Import::2019-07-29 (1639)